Ameliorative effect of hesperidin on streptozotocin‐diabetes mellitus‐induced testicular DNA damage and sperm quality degradation in Sprague–Dawley rats - Aksu, Emrah Hicazi; Kandemir, Fatih Mehmet; Küçükler, Sefa (Wiley, 2021)
This study aimed to investigate the effect of hesperidin on reproductive damage caused by diabetes mellitus. A total of 24 adult male rats were divided into four groups: control group, hesperidin group, diabetes mellitus group, and diabetes mellitus + hesperidin group. The study was conducted for 4 weeks. At the end of the study, the rats were sacrificed and testicular oxidative stress markers (MDA, GSH, GSH-Px, SOD, and CAT), DNA damage in testes (8-OHdG), and routine sperm parameters were evaluated. According to the results of the study, most of the parameters were similar in the control and hesperidin groups but CAT activity in the hesperidin group was statistically higher than the control group. Also, diabetes mellitus (DM) significantly increased MDA levels and decreased enzymatic antioxidant (GSH-Px, SOD, CAT) activities and nonenzymatic (GSH) antioxidant levels. On the other hand, hesperidin supplementation significantly decreased oxidative stress and increased enzymatic antioxidant activities and nonenzymatic antioxidant levels due to the antioxidant effect. Also, DM increased DNA damage levels in testicular tissue and hesperidin supplementation significantly decreased DNA damage levels in testes of diabetic male rats. Besides, sperm motility significantly decreased while abnormal sperm rate and dead sperm rate were significantly increased in diabetic rats. Hesperidin supplementation significantly reduced these side effects in diabetic rats. In conclusion, hesperidin supplementation could be beneficial for decreasing the side effects on the male reproductive system caused by DM in rats. PRACTICAL APPLICATIONS: Diabetes is an important metabolic disease, affecting quality of life and fertility. Hesperidin has an antioxidant effect and has a potential protective effect on reproductive toxicity in diabetic male rats. Hesperidin decreased oxidative stress, and DNA damage in testis resulted from hyperglycemia and improved sperm quality in diabetic rats. The hesperidin supplementation could be a good strategy to protect male fertility in diabetic patients.
Keywords: Male; Hesperidin; Spermatozoa; Streptozocin; Diabetes Mellitus, Experimental; Rats; Rats, Sprague-Dawley; Testis; Quality of Life; Sperm Motility; Animals; Humans; DNA Damage; 3. Good health